Generation of Lactose- and Protease-Positive Probiotic Lacticaseibacillus rhamnosus GG by Conjugation with Lactococcus lactis NCDO 712 - Hussain, Nazar (Appl Environ Microbiol, 2021)
Lacticaseibacillus rhamnosus GG (LGG) is the most studied probiotic bacterium in the world. It is used as a probiotic supplement in many foods, including various dairy products. However, LGG grows poorly in milk, as it neither metabolizes the main milk carbohydrate lactose nor degrades the major milk protein casein effectively. In this study, we made L. rhamnosus GG lactose and protease positive by conjugation with the dairy Lactococcus lactis strain NCDO 712 carrying the lactose-protease plasmid pLP712. A lactose-hydrolyzing transconjugant colony was obtained on agar containing lactose as the sole source of carbohydrates. By microscopic analysis and PCR with LGG- and pLP712-specific primers, the transconjugant was confirmed to have originated from LGG and to carry the plasmid pLP712. The transconjugant was named L. rhamnosus LAB49. The isolation of plasmids revealed that not only pLP712 but also other plasmids had been transferred from L. lactis into LGG during conjugation. With plasmid-specific PCR primers, four additional lactococcal plasmids were detected in LAB49. Proteolytic activity assay and SDS-PAGE analysis verified that L. rhamnosus LAB49 effectively degraded β-casein. In contrast to its parental strain, LGG, the ability of LAB49 to metabolize lactose and degrade casein enabled strong and fast growth in milk. As strains with new properties made by conjugation are not regarded as genetically modified organisms (GMOs), L. rhamnosus LAB49 could be beneficial in dairy fermentations as a probiotic starter culture. IMPORTANCE Probiotic strain Lacticaseibacillus rhamnosus GG (LGG) is widely sold on the market as a probiotic or added as a supplement in dairy foods because of its benefits in human health. However, due to the deficiency of lactose and casein utilization, LGG does not grow well in milk. On the other hand, lactose intolerance and cow’s milk protein allergy are the two major problems related to milk consumption. One option to help with these two conditions is the use of probiotic or lactose- and casein-hydrolyzing bacteria in dairy products. The purpose of this study was to equip LGG with lactose/casein-hydrolyzing ability by bacterial conjugation. As a result, we generated a non-GMO LGG derivative with improved properties and better growth in milk.